(untitled) (Scientific journal of the Fergana State University, 2024)
The purpose of the study is to determine the development of scientific and practical solutions aimed at increasing soil fertility while determining the agrochemical properties of soils in the gray earth and desert zones of the Fergana Valley. The studies were carried out using methods for placing soil sections along a geochemical-geographical section, according to standard methods generally accepted in soil science in field, laboratory and office conditions; the studies used morphological, comparative-historical, chemical-analytical and profile methods, including chemical analysis according to the recipe “Guide to chemical analysis of soils” E.V. Arinushkina. Research results. Based on the results of an analysis of the amount of nutrients in soils, it was established that fertility indicators in the zone of gray earth and desert soils are average and below average in terms of gross and mobile quantities of humus, nitrogen, phosphorus and potassium. Relatively high fertility has been preserved in the soils of the serozomic zone. Conclusions. Currently, the degree of soil fertility has reached a stable level in soils in gray soil and desert zones. Soil fertility in the gray soil region is mainly associated with the improvement of agricultural practices aimed at increasing productivity and improving the physical properties of the soil. In the desert zone, along with these measures, it is necessary to apply measures such as reducing soil salinity and lowering the level of mineralized water.